The Combination of Phages and Faecal Microbiota Transplantation Can Effectively Treat Mouse Colitis Caused by Salmonella enterica Serovar Typhimurium - Wang, Xinwu; Xing, Yating; Ji, Yalu; Xi, Hengyu; Liu, Xiaohe; Yang, Li; Lei, Liancheng; Han, Wenyu; Gu, Jingmin (Frontiers in Microbiology, 2022)
Salmonella enterica serovar Typhimurium (S. Typhimurium) is one of the common causes of human colitis. In the present study, two lytic phages vB_SenS-EnJE1 and vB_SenS-EnJE6 were isolated and the therapeutic effect of the combination of phages and faecal microbiota transplantation (FMT) on S. Typhimurium-induced mouse colitis was investigated. The characteristics and genome analysis indicated that they are suitable phages for phage therapy. Results showed that vB_SenS-EnJE1 lysis 41/54 Salmonella strains of serotype O4, and vB_SenS-EnJE6 lysis 46/54 Salmonella strains of serotypes O4 and O9. Severe inflammatory symptoms and disruption of the intestinal barrier were observed in S. Typhimurium -induced colitis. Interestingly, compared with a single phage cocktail (Pc) or single FMT, the combination of Pc and FMT (PcFMT) completely removed S. Typhimurium after 72 h of treatment, and significantly improved pathological damage and restored the intestinal barrier. Furthermore, PcFMT effectively restored the intestinal microbial diversity, especially for Firmicutes/Bacteroidetes (predominantly bacterial phyla responsible for the production of short-chain fatty acids (SCFA)). Additionally, we found that PcFMT treatment significantly increased the levels of SCFA. All these data indicated that the combination of phages and FMT possesses excellent therapeutic effects on S. Typhimurium -induced intestinal microbiota disorder diseases. Pc and FMT played roles in “eliminating pathogens” and “strengthening vital qi”, respectively. This study provides a new idea for the treatment of intestinal microbiota disorder diseases caused by specific bacterial infections.